Raul Lino and the decorative program of the Primary School of Alcântara – Lisboa (1917) - Manique da Silva, Carlos Miguel (Historia y Memoria de la Educación, 2020)
Using as a reference the Primary School of Alcântara (Lisbon) – designed in 1815 by the architect Raul Lino and inaugurated one year later –, my analysis will focus on the decorative program (set of paintings, dated from 1917) on the walls of the classrooms of this building. My main goal is to examine the impact that the paintings, from the perspective of their author - Raul Lino, whose Anglo German education was strongly influenced by the Arts & Crafts movement – would have on the children. For the architect, images was not just decorative. In fact, they were meant to help the children appreciate nature and art, to educate their sense of taste, and even to develop in them a patriotic sense (an agenda involving the formation of the republican citizen). In this sense, we see the emergence the of an aesthetic education as part of a more general social and political program. In line with the same idea, we can conceive of the curriculum in a wider sense, i. e., as including knowledge and skills obtained in formal lessons, but also values and attitudes received from the impact of school decoration on the students individual and collective memory. Methodologically, itis worth emphasizing that the sources I value are not just visual. In fact, some written texts by Raul Lino, namely, active correspondence and articles, are also used; the triangulation of several sources of evidence is very important. The analysis of the visual sources goes from the description of the elements present in the paintings (mostly, Nature and animals) to close observation of the sources that inspired the author. In relation to this last aspect, I should underline that Raul Lino was an illustrator of children’s books, an experience that he integrated into the school buildings that he planned.